Live life in crescendo : your most important work is always ahead of you - Covey, Stephen R.; Haller, Cynthia Covey (Simon & Schuster, 2022)
"Stephen R. Covey spent his long and storied career inspiring millions of individuals to make their lives more effective, compassionate, and meaningful. Near the end of his life, Covey felt there was a final component to his work: How to live your best life no matter your age? How to best respond to life-challenging experiences? How to approach the challenges and opportunities of middle to later life--like raising children, caring for your parents, leading and inspiring others, staying on top of your career, contributing to your community, and what follows next? Live Life in Crescendo is Covey's answer to these questions, outlining his vision for those in the prime of life, whatever age you may be. Covey urges all to "live life in crescendo," continually growing in contribution, learning, and influence. In the same way that music builds on the previous notes, life too, builds on the past and unfolds in the future. This crescendo mentality urges you to use whatever you have--your time, talents, resources, gifts, passion, money, and influence--to enrich the lives of people around you, including your family, neighborhood, community, and the world"--